STUDI TENTANG PEKERJA WANITA DI KOTA PALU (Studi Kasus Pada Ibu Rumah Tangga di Industri Tenun) - Rioeh, Irwan Dwi Sukanda Putra (Katalogis, 2017)
The research aims to: (1) find out and analyze factors that support working women in weaving industry in Palu; (2) find out the factors that influence women income in weaving industry in Palu; (3) find out and analyze the income proportional and working women income in industry on total income of household. Population was working women or housewives live in Ulujadi district who devote their time at business sector called weaving industry of Sarong Donggala numbered 27 women selected throught census. The data were analyzed using descriptive qualitative analysis. The research results indicate that: 1) the factors support the women (housewives) working in weaving industry in Palu is time devotion and income level; (2) that factors influence working women income in weaving industry in Palu is age of them, the length of work and experience of the work; and (3) the proportional of household income received by the working women (housewives) in weaving industry in Palu is 34.78 percent of non weaving silk or sourced from husband income is 65.22 percent of total household income is Rp.2.300.000,-.